ANTHRACYCLINE TOXICITY IN CANCER THERAPY: BALANCING EFFICACY AND SAFETY (Journal of Medical & Health Sciences Review, 2025)
Toxicity associated with anthracycline derivatives presents significant challenges to cancer therapy. Despite their proven efficacy against various malignancies, possible adverse effects on cardiovascular and hematopoietic systems must be carefully considered when making clinical decisions. Although anthracyclines remain important in cancer therapy, the search for safer alternatives and individualized treatment strategies is of utmost importance to prevent toxicities like cardiotoxicity, nephrotoxicity, and neurotoxicity. Careful monitoring, the addition of cardioprotective measures, and the study of prognostic biomarkers are important factors to reduce the risks associated with the use of anthracyclines. Taken together, the complex interplay between therapeutic benefit and potential toxicity highlights the importance of a nuanced and individualized approach to anthracycline-based therapies. This review highlights the critical need for continued research and development of therapeutic approaches to address their toxicity. By promoting continuous research and adopting innovative solutions, the medical community can strive to optimize the balance between therapeutic efficacy and minimization of unwanted effects of anthracycline derivatives to improve cancer treatment.